Pengaruh Model Pembelajaran Kooperatif Tipe STAD terhadap Hasil Belajar Matematika Materi Jam Kelas 3 SDN Keleyan 4 Bangkalan - Hamida, Rika Nur; Hani, Roukhil Ummu; Avisenna, Emilda Shofiyah; Rohman, Achmad Habibur; Susilowati, Diana; Pratikno, Ahmad Sudi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to investigate how implementing the STAD cooperative learning model influences the mathematics learning outcomes of third-grade students at SDN Keleyan 4 Bangkalan, specifically focusing on the topic of fractions. The research utilizes a quasi-experimental approach. The sampling technique used was saturated sampling, in which the entire population of 20 third-grade students at SDN Keleyan 4 Bangkalan was taken as the research sample. Data collection methods encompass interviews, observations, as well as pretests and posttests. Analysis of the collected data involves using the paired sample t-test, preceded by a test for normality. The results, conducted at a confidence level of ???? = 5% with degrees of freedom (df) = 19, indicate a calculated t-value of 6.469, exceeding the critical t-value of 1.729 (t-count > t-table). Hence, it can be inferred that employing the STAD cooperative learning model in teaching mathematics at SDN Keleyan 4 Bangkalan positively impacts student learning outcomes.